Use of Assistive Technology for Cognition Among People With Traumatic Brain Injury: A Survey Study. Issue 6 (1st June 2016) - Wang, Jing; Ding, Dan; Teodorski, Emily E.; Mahajan, Harshal P.; Cooper, Rory A.
ABSTRACT: A survey was designed and administered in this study to assess the use of assistive technology for cognition (ATC), especially portable electronic ATC, among veterans with traumatic brain injury (TBI). The aim of the survey was to obtain information on current ATC devices and applications use, users' experience with different features of ATC, and relevant training/support for their ATC. Twenty-nine veterans with TBI participated in this study. Results showed that portable electronic ATC, especially smartphones and a variety of apps, were widely used by the participants to compensate for cognitive limitations. Portable electronic devices such as smartphones and smart pads received higher usability ratings than paper-based tools. More than 75% of participants did not go through a service delivery process for these electronic ATC. The information collected in the study provided a more updated picture of ATC use, especially portable electronic ATC use, among people with TBI. It also potentially informs the future development of ATC and supports the need for training and an appropriate acquisition process of portable electronic ATC devices.